A Note on the Theory of Investment and Production - Miller, Roger F. (Quarterly Journal of Economics, 1959)
Journal Article A Note on the Theory of Investment and Production Get access Rogue F. Miller Rogue F. Miller University of Wisconsin Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 73, Issue 4, November 1959, Pages 672–681, https://doi.org/10.2307/1884310 Published: 01 November 1959